Software tools for automated transmission electron microscopy - Schorb, Martin; Haberbosch, Isabella; Hagen, Wim; Schwab, Yannick (Nature methods, 2019)
Py-EM and SerialEM enable automated microscope control for high-throughput data acquisition in diverse transmission electron microscopy imaging experiments.
Gesehen am 25.06.2019